PERAN GURU PAI DALAM MENANAMKAN KEDISIPLINAN BERIBADAH SISWA - Lubis, Nazlina Rahmi (Jurnal Al-Fatih, 2024)
This research aims to describe the role of Islamic Education teachers in instilling discipline in students' worship. This study uses field research methods with a qualitative approach. The study subjects are the school principal and Islamic Education teachers from grades I to VI. This research was conducted at Al-Washliyah 83 Gunting Saga Elementary School. Data collection techniques include observation, interviews, and documentation. The data analysis technique involves data reduction, data presentation, and data verification. The results show that the role of teachers in instilling worship discipline involves conveying to students through habituation, which is everything done repeatedly that can enhance individual awareness as a servant obedient to their Creator and can form students with good character. Furthermore, the teacher serves as a role model. The teacher becomes the best example for their students and strives to demonstrate positive attitudes and behaviors. The factors that support students' discipline in worship are the awareness that grows from within the students, motivation and support, adequate facilities and infrastructure, and a good family environment. Meanwhile, the hindering factors include a lack of understanding of Islamic teachings, environmental influences, excessive use of mobile phones, and the emergence of a lazy attitude.